2012
DOI: 10.2183/pjab.88.192
|View full text |Cite
|
Sign up to set email alerts
|

Hepatorenal tyrosinemia

Abstract: In 1957 Sakai and Kitagawa in Japan reported the clinical and biochemical findings in a patient with tyrosinemia, tyrosyluria, liver cirrhosis, and renal rickets. Subsequently, reports were published from various countries of other patients with hepatorenal tyrosinemia (HRT). 4-Hydroxyphenylpyruvate dioxygenase deficiency was originally proposed as the cause of HRT. However, in 1977 Lindblad et al. found that succinylacetone, which accumulates in the serum and urine from patients with HRT, inhibits delta-amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…One of the first patients described with TT1 presented with liver cirrhosis, renal tubular defects, and vitamin D-resistant rickets, although the exact diagnosis was not clear at that time [1]. Initially, the primary enzyme defect was considered to be a defect of 4-hydroxyphenylpyruvate dioxygenase (4HPPD) [2, 3]. Some years later, it became apparent that the primary enzyme deficiency was located more downstream in the catabolic pathway of tyrosine at FAH (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…One of the first patients described with TT1 presented with liver cirrhosis, renal tubular defects, and vitamin D-resistant rickets, although the exact diagnosis was not clear at that time [1]. Initially, the primary enzyme defect was considered to be a defect of 4-hydroxyphenylpyruvate dioxygenase (4HPPD) [2, 3]. Some years later, it became apparent that the primary enzyme deficiency was located more downstream in the catabolic pathway of tyrosine at FAH (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The renal disease may progress with nephrocalcinosis and glomerulosclerosis to chronic renal failure. Renal disease may be the predominant feature; however, there is always some co-existing liver disease of variable severity [7]. Patients may present in infancy, childhood and as adults, and the age at onset broadly correlates with disease severity [2].…”
Section: Introductionmentioning
confidence: 99%
“…In 1957, Japanese scientists, Kiyoshi Sakai and colleagues, published three reports describing the clinical, biochemical, and pathological findings of a 2-yearold boy with hepatorenal tyrosinemia who was then thought to have an "atypical" case of tyrosinosis ("atypical" because it differed from the supposedly prototypical case reported by Medes) [13][14][15][16].…”
Section: Historymentioning
confidence: 99%
“…Furthermore, in 1964 several pediatricians in Chicoutimi (Quebec-Canada) became aware of an increased incidence of infantile liver cirrhosis that was later recognized to be due to hereditary tyrosinemia type [21,22]. Both the Scandinavian and Canadian groups suggested that the Japanese patients described earlier by Sakai and colleagues had the same disorder, that is, HT-1 [16]. Therefore, it has been considered that the first definite case report in the world of HT-1 was in Japan by Sakai and colleagues in 1957 [23].…”
Section: Historymentioning
confidence: 99%